(untitled) (Bangladesh Journal of Agricultural Research, 2009)
An experiment was conducted to study the effect of chlorine, packaging and storage conditions on quality and shelf life of tomato. Tomato treated with chlorine; packed in perforated (0.25%) polyethylene bag and kept at ambient (Temperature 20-25Â°C & relative humidity 70-90%) condition resulted in substantial reduction in losses caused by decay and weight loss. This treatment combination also considerably delayed compositional changes in TSS, total sugar, reducing sugar, vitamin-C, B-carotene, etc. Under this condition, shelf life of tomato had extended upto 17 days as compared to non-treated and kept in ambient condition without packaging or packed in gunny bag for 7 days only. Key Words: Postharvest treatments, shelf-life, quality of tomato. doi: 10.3329/bjar.v33i4.2291 Bangladesh J. Agril. Res. 33(4) : 579-585, December 2008